Lyophilised human cord blood leukoconcentrate triggers formation of dendritic cells with a tolerogenic phenotype - Goltsev, Anatoliy; Dubrava, Tetyana; Lutsenko, Olena; Sokil, Larysa; Chernyshenko, Lyudmyla; Grisha, Ihor (Problems of Cryobiology and Cryomedicine, 2026)
In this research we investigated the lyophilized human cord blood leukoconcentrate (lHCBL) as an inducer of the in vitro formation of dendritic cells (DCs) with a tolerogenic phenotype, obtained from native mononuclear cells (MNCs) of the animals’ bone marrow. The phenotypic affiliation of DCs to tolerogenic was assessed by the expression of markers characteristic of them: CD11b, CD80, CD86, CD14, and CD83. To form the tolerogenic phenotype of DCs, lHCBL was additionally added to the RPMI-1640 culture medium containing mouse recombinant GM-CSF, IL-4 and dexamethasone in different doses (1x 103, 1x 104 and 1x 105 cells/ml). A dose-dependent effect of lHCBL on the in vitro formation of DCs with phenotypic features of tolerogenic cells from bone marrow MNCs was established. The conditions for obtaining DCs in vitro under the influence of LHCBL with the maximum tolerogenic effect were determined, that was manifested by a significant decrease in the expression level of co-stimulatory molecules CD80 and CD86 (by 1.6 times), an increase in CD11b (by 1.2 times) and the content of CD11b+-DCs (by 25%) compared to the control values, that confirms the tolerogenic phenotype of the obtained cells. This fact indicates a limitation of the ability of DCs formed in culture to implement cooperative interactions and activation of T-effector cells. Probl Cryobiol Cryomed. 2026; 36(1): 51—57